2013
DOI: 10.7146/ocps.v14i1.5170
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of “Writing for Learning” in a Nursing Program.

Abstract: This article explores the activity of writing in higher education as a mediational means for student meaning making. From a dialogic perspective, writing is not about learning and applying formulas and making fixed kinds of texts, but about ways of working and ways of acting that brings writers, readers, resources and contexts into trajectories. The argument is that processes of writing enhance student meaning making and that these processes are formed by complex interaction. Contextual interpretation and use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This finding can reflect the different demands and appreciations of research but also points to the gaps between learning to do and learning to learn, discourses that vary in the contexts of university and clinical healthcare. 33,34,51 Activity theory assumes that all kinds of learning activities serve what is historically and culturally acknowledged knowledge by members of a group. 33,34,52 Therefore, the debate about teaching and learning academic writing for the purpose of the product or a degree and research consumption raises questions about whether the academization is taking place at the cost of the fundamental and pragmatic purposes of nursing.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding can reflect the different demands and appreciations of research but also points to the gaps between learning to do and learning to learn, discourses that vary in the contexts of university and clinical healthcare. 33,34,51 Activity theory assumes that all kinds of learning activities serve what is historically and culturally acknowledged knowledge by members of a group. 33,34,52 Therefore, the debate about teaching and learning academic writing for the purpose of the product or a degree and research consumption raises questions about whether the academization is taking place at the cost of the fundamental and pragmatic purposes of nursing.…”
Section: Discussionmentioning
confidence: 99%
“…33,34,51 Activity theory assumes that all kinds of learning activities serve what is historically and culturally acknowledged knowledge by members of a group. 33,34,52 Therefore, the debate about teaching and learning academic writing for the purpose of the product or a degree and research consumption raises questions about whether the academization is taking place at the cost of the fundamental and pragmatic purposes of nursing. 44 We found that writing a BT facilitated the students' understanding of individual patients and the bodily mechanisms justifying nursing care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations